Genome and bioethics: an hollistic vision of the way we march Towards the happy world biosciences promise - M.J. Antoine, Jean-Luc (Acta Bioethica, 2004)
The idea of an utopian city is almost as old as human thinking. It consists in a society theoretically perfect and transparent where everything is under control, so that citizens could achieve happiness. In this article, using a historical perspective, we pretend to reflect, with practical examples such as cloning, stem cells and eugenics, on a genetic society which is blossoming and in spite of presenting itself as a strong tool to achieve the utopian city, this would not be possible due to the warning for many risks and dangers. Therefore we believe it is important to carry out an analysis on bioethics and progress, before moving on.